Legacies of victimization: Evidence from forced resettlement in Zimbabwe - Shelley Liu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
How does wartime victimization shape victims' political attitudes in the long run? We argue that violence increases politics' salience to victimized communities, which in turn increases these communities' political awareness and evaluation of governance quality decades after war has ended. We examine Protected Villages in the Zimbabwe Liberation War (1972-79). Protected Villages, a Rhodesian counterinsurgency strategy, was a large-scale resettlement programme designed to cut off rebel-civilian interactions, but it intensified civilian support for the eventually victorious rebel group. Using archival data, we map pre-war to current-day administrative divisions to Protected Villages-affected areas and estimate a difference-in-discontinuities regression to identify Protected Villages' long-run effects. We find that Protected Villages-affected areas have a greater awareness of the country's political development today and are more critical of poor government performance. Contrary to two major strands of the conflict literature, we find no evidence of increased political participation and pro-social behaviour in the long run, nor hardened support for the ruling party-which these areas had supported during the war.
Keywords: 330; victimization; political awareness; Zimbabwe Liberation War; Protected Villages